Extracorporeal membrane oxygenation seems to induce impairment of primary hemostasis pathology as measured by a Multiplate analyzer: An observational retrospective study - Garaj, Michal; Durila, Miroslav; Vajter, Jaromir; Solcova, Michaela; Marecek, Frantisek; Hrachovinová, Ingrid (Artificial organs, 2022)
BACKGROUND: Extracorporeal membrane oxygenation (ECMO) support is often associated with bleeding complications caused by secondary or primary hemostasis pathology. However, there are limited data investigating primary hemostasis using Multiplate aggregometry with specific diagnostics tests for vWF (von Willebrand factor) deficiency. AIMS: The aim of this study was to find out whether short-term ECMO produces the pathology of primary hemostasis that is detected by Multiplate aggregometry and to investigate the pathology of vWF. METHODS: In this study, blood samples of 20 patients undergoing lung transplantations with short-term perioperative ECMO support were analyzed. The multimeric structure, the levels of von Willebrand factor antigen (vWF), ristocetin cofactor (RCo), collagen-binding protein (CB), and the results of multiple electrode aggregometry RISTO (ristocetin), ADP (adenosine diphosphate), ASPI (Aspirin®; arachidonic acid), and TRAP (thrombin receptor activating peptide) tests were compared to the samples obtained before and after ECMO support. RESULTS: The Multiplate ADP and RISTO tests showed the presence of significant pathology in primary hemostasis after surgery (p < 0.05), suggesting the presence of acquired platelet dysfunction. Although the RISTO tests suggest the presence of acquired vWF deficiency, laboratory tests for vWF antigen and RCo and CB tests showed an increase in this case. The multimeric structure of vWF did not show clinically significant deterioration. CONCLUSIONS: Multiple aggregometry ADP, ASPI, and TRAP tests seem to be able to detect primary hemostasis pathology (platelets aggregation and adhesion pathology) that is present during short-term perioperative ECMO support in lung transplantation procedures. Interestingly, RISTO tests seem to be more suitable for the diagnosis of platelet dysfunction than the diagnosis of acquired vWF deficiency in this situation.
Keywords: Retrospective Studies; retrospektivní studie; Blood Platelet Disorders; von Willebrand Factor; von Willebrand Diseases; hemostáza; adenosindifosfát; mimotělní membránová oxygenace; Hemostasis; von Willebrandova nemoc; Adenosine Diphosphate; Extracorporeal Membrane Oxygenation; Humans; lidé; von Willebrandův faktor; trombocytopatie